Liquid crystal polyarylester conveying belt and preparation method of covering layer of liquid crystal polyarylester conveying belt

By adopting the belt core structure of liquid crystal polyaryl fiber and nylon filament in the liquid crystal polyaryl conveyor belt, and adding modified chopped fibers and composite flame retardant to the cover layer, the problem of insufficient tensile strength of the fabric core flame retardant conveyor belt and the problem of combining the cover layer is solved, and the overall performance and safety of the conveyor belt are improved.

CN120553316AActive Publication Date: 2025-08-29ZHEJIANG DOUBLE ARROW RUBBER
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510716467.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-30
Publication Date
2025-08-29
Estimated Expiration
2045-05-30

AI Technical Summary

Technical Problem

The tensile strength of existing fabric core flame retardant conveyor belts is insufficient, making it difficult to meet the working conditions of high tensile strength, and it is difficult to combine the cover layer with fiber material.

Method used

The core structure of liquid crystal polyaryl fibers as warp yarns and nylon filaments as weft yarns is used, and modified chopped fibers, thermoplastic polyurethane elastomers, nanoclays and composite flame retardants are added to the cover layer to fix the cover layer by interlayer adhesives, and the cost is reduced using recycled materials.

Benefits of technology

The tensile strength of the belt core and cover layer is improved, the wear resistance and durability of the overall conveyor belt is enhanced, the production cost is reduced, and the double flame retardant effect of gas-phase-condensing phase is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005428348260000051
    Figure BDA0005428348260000051
Patent Text Reader

Abstract

The invention provides a liquid crystal polyarylester conveying belt and a preparation method of a covering layer of the liquid crystal polyarylester conveying belt, the conveying belt comprises a liquid crystal polyarylester fabric belt core and the covering layer fixed on the surface of the belt core through an interlayer adhesive, and the belt core takes liquid crystal polyarylester fibers as warp yarns and nylon filaments as weft yarns; the covering layer is prepared from components in parts by mass as follows: 55-70 parts of synthetic rubber, 30-40 parts of natural rubber, 5-15 parts of a thermoplastic polyurethane elastomer, 2-6 parts of chopped fibers, 5-8 parts of a reinforcing agent, 0.5-0.8 parts of nano argil, 2-4 parts of a smoke suppressant and 5-10 parts of a flame retardant; the chopped fibers comprise liquid crystal polyarylester fibers, and the chopped fibers are modified by adopting sodium monoalkyl ether phosphate or potassium dodecyl phosphate. The belt core has high tensile strength, the tensile strength is improved by adding the modified chopped fibers of the liquid crystal polyarylate fibers into the material of the covering layer, so that the overall tensile strength of the conveying belt is further improved, and the belt core has good market prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of mine transfer equipment, and particularly relates to a liquid crystal polyarylate conveyor belt and a preparation method of a covering layer thereof. Background Art

[0002] Among the flame-retardant conveyor belts used in coal mines in my country, fabric core flame-retardant conveyor belts or steel cord core conveyor belts are generally used. Compared with steel cord core conveyor belts, fabric core flame-retardant conveyor belts are light in weight, low in production cost, easy to maintain and replace, relatively easy to connect, and safe to use. However, since the belt core is made of fabric fibers such as nylon fiber, cotton fiber, and polyarylate fiber, the strength is relatively low and it is difficult to adapt to working conditions with high tensile strength requirements. Although the steel cord core flame-retardant conveyor belt has high tensile strength, it is heavy and sometimes longitudinal tearing occurs. Moreover, it cannot be disconnected when the conveyor belt is ignited, which easily causes the fire to spread along the conveyor belt. It can be seen that the fabric core flame-retardant conveyor belt has obvious advantages in general application scenarios. If the tensile strength of the fabric core flame-retardant conveyor belt can be further improved, it may further replace the steel cord core flame-retardant conveyor belt. The traditional conveyor belt with ordinary rubber as the covering layer and cotton fiber fabric core is a kind of low strength, poor durability, high transportation energy consumption and large production pollution. With the development of high-performance fiber materials, high-strength and high-modulus fiber materials such as aramid, LCP fiber, and ultra-high molecular weight polyethylene have begun to be used in fabric core flame-retardant conveyor belts. Among them, liquid crystal polyarylate fiber with lighter weight, higher strength, smaller shrinkage and better durability has the best performance in fabric core flame-retardant conveyor belts. However, due to the large steric hindrance effect between the amide bonds in polyarylate fiber, it is difficult for it to form hydrogen bonds with other materials, resulting in poor fiber surface activity, making it difficult for the belt core made of polyarylate fiber material to combine with the covering layer.

[0003] Patent application number CN2025100669837 discloses a flame-retardant polyarylate fabric conveyor belt with a core impregnation compound, which is then plasticized to form a plasticized core. The cover layer is dynamically vulcanized and bonded to the plasticized core under hot conditions to create a flame-retardant polyarylate fabric conveyor belt. The polyarylate fabric core of this belt is constructed from polyarylate fibers, resulting in high strength, a thin belt body, and low weight. The finished belt weighs approximately 50% of a steel cord conveyor belt of equivalent strength. Overall, the tensile strength of this flame-retardant polyarylate fabric conveyor belt still has room for improvement to allow for its application in more demanding applications.

[0004] If the tensile strength of the covering layer can be enhanced to a certain extent, the overall tensile strength of the fabric core flame retardant conveyor belt can also be enhanced, making up for the lack of tensile strength of the fabric belt core. Summary of the Invention

[0005] The object of the present invention is to provide a liquid crystal polyarylate conveyor belt and a preparation method thereof and a covering layer material added with liquid crystal polyarylate chopped fibers.

[0006] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0007] A liquid crystal polyarylate conveyor belt comprises a liquid crystal polyarylate fabric belt core and a covering layer fixed to the surface of the belt core via an interlayer adhesive. The liquid crystal polyarylate fabric belt core comprises liquid crystal polyarylate fibers as warp yarns and nylon filaments as weft yarns. The covering layer rubber material comprises the following components, measured by mass: 55-70 parts of synthetic rubber, 30-40 parts of natural rubber, 5-15 parts of thermoplastic polyurethane elastomer, 2-6 parts of chopped fibers, 5-8 parts of white carbon black, 0.5-0.8 parts of nanoclay, 2-4 parts of a smoke suppressant, and 5-10 parts of a flame retardant. The chopped fibers comprise liquid crystal polyarylate fibers, and are modified using sodium monoalkyl ether phosphate or potassium lauryl phosphate.

[0008] Preferably, the smoke suppressant includes a molybdate smoke suppressant or zinc borate, and the reinforcing agent includes carbon black or white carbon black.

[0009] Preferably, the flame retardant is compounded with aluminum hydroxide and decabromodiphenyl ether, wherein the proportion of decabromodiphenyl ether in the flame retardant is 2-4%.

[0010] Preferably, the chopped fibers have a length of 1-5 mm.

[0011] Preferably, the chopped fibers are made from recycled scrapped liquid crystal polyarylate ropes, and the content of liquid crystal polyarylate fibers in the recycled liquid crystal polyarylate ropes is not less than 60%.

[0012] Preferably, the ratio of the synthetic rubber to the natural rubber is 6:4±0.2.

[0013] Preferably, the synthetic rubber includes styrene-butadiene rubber and / or butadiene rubber.

[0014] A method for preparing a covering layer material for a liquid crystal polyarylate conveyor belt, characterized in that it comprises the following steps:

[0015] S1. Preparation of chopped fibers: Cut the scrapped liquid crystal polyarylate rope into segments and disassemble them. Soak them in a neutral detergent at 50-80°C for 20-40 minutes. During the soaking period, rub and scrub the scrapped liquid crystal polyarylate rope to further remove impurities on the scrapped liquid crystal polyarylate rope. Then, remove the scrapped liquid crystal polyarylate rope from the cleaning process, clean it, and dry it. Immerse the scrapped liquid crystal polyarylate rope after preliminary cleaning in 0.5-2 mol / L dilute sulfuric acid or dilute hydrochloric acid. Soak the scrapped liquid crystal polyarylate rope in an ultrasonic environment for 10-20 minutes to further clean it. Washing and increasing the roughness of the fiber surface of the scrapped liquid crystal polyarylate rope, then rinsing and drying; inspecting the cleaned scrapped liquid crystal polyarylate rope, cutting off the portion with residual impurities, then cutting the scrapped liquid crystal polyarylate rope to obtain chopped fibers with a length of 1-5 mm, and thoroughly kneading the chopped fibers; putting the chopped fibers into a mesh bag, soaking them in a modifier solution at a temperature of 50-70° C. for 2-5 minutes, removing them from the bag and draining them naturally, and then drying them at 80-85° C. for 2 hours for later use;

[0016] S2. The natural rubber is first masticated, and then the synthetic rubber and thermoplastic polyurethane elastomer are added and mixed evenly;

[0017] S3. Adding chopped fibers, reinforcing agent and nano-clay;

[0018] S4. Add flame retardants and smoke suppressants.

[0019] Preferably, in S1, the modifier solution is a monoalkyl ether phosphate sodium salt or a potassium dodecyl phosphate aqueous solution with a mass concentration of 2-4%.

[0020] Preferably, in S3, the nanoclay and the chopped fibers obtained in S1 are premixed and sprayed with a silane coupling agent, wherein the amount of the silane coupling agent is 0.5%-1% of the mass of the chopped fibers obtained in S1; the treated chopped fibers are then mixed with 1 / 4-1 / 3 of the rubber compound obtained in S2, followed by adding a reinforcing agent, and then adding the remaining rubber compound in 1-3 steps for mixing.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The belt core uses liquid crystal polyarylate fiber as warp yarn and nylon filament as weft yarn, taking into account both tensile strength and cost control;

[0023] 2. In the cover material, the wear resistance and aging resistance of the cover material are improved by adding thermoplastic polyurethane elastomer;

[0024] 3. By adding modified short fibers containing liquid crystal polyarylate fibers, the tensile strength and durability of the cover layer are enhanced, and longitudinal tearing is less likely to occur;

[0025] 4. Due to the high cost of liquid crystal polyarylate fibers, the core cost is reduced by using nylon filaments as weft yarns, and the cover cost is reduced by using recycled materials to prepare chopped fibers;

[0026] 5. A flame retardant compounded with aluminum hydroxide and decabromodiphenyl ether achieves dual flame retardancy in the gas phase and condensed phase, and zinc borate is further used to achieve both smoke suppression and flame retardancy.

[0027] 6. The combination of a belt core with higher tensile strength and a cover layer with higher tensile strength further improves the overall tensile strength of the liquid crystal polyarylate conveyor belt. DETAILED DESCRIPTION

[0028] The following describes embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention by the content disclosed in this specification. The present invention can also be implemented or applied by other different specific embodiments, and the various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. Unless otherwise stated, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. Unless otherwise stated, the reagents and materials used in the present invention are commercially available.

[0029] Example 1

[0030] A liquid crystal polyarylate conveyor belt, comprising a liquid crystal polyarylate fabric belt core and a covering layer fixed to the surface of the belt core by an interlayer adhesive. The liquid crystal polyarylate fabric belt core comprises liquid crystal polyarylate fibers as warp yarns and nylon filaments as weft yarns. The covering layer material comprises the following components, measured by mass: 60 parts of butadiene rubber, 40 parts of natural rubber, 8 parts of thermoplastic polyurethane elastomer, 2-6 parts of chopped fibers, 5 parts of white carbon black, 0.8 parts of nanoclay, 3 parts of zinc borate, 6 parts of aluminum hydroxide, and 0.2 parts of decabromodiphenyl ether.

[0031] The chopped fibers include liquid crystal polyarylate fibers and are modified with sodium monoalkyl ether phosphate or potassium lauryl phosphate. Industrial-grade sodium monoalkyl ether phosphate and potassium lauryl phosphate are both priced at less than 40 yuan per kilogram, making them relatively inexpensive. In this embodiment, the more affordable 45% potassium lauryl phosphate is used.

[0032] The length of the chopped fibers is 1-5 mm.

[0033] The chopped fibers are made from recycled, scrapped liquid crystal polyarylate ropes, with the scrapped liquid crystal polyarylate rope containing no less than 60% liquid crystal polyarylate fiber. In this embodiment, a liquid crystal polyarylate rope used for ship mooring, scrapped after four years of use, was used. The rope contained 100% liquid crystal polyarylate fiber and had a single filament diameter of 60 μm.

[0034] A method for preparing a covering rubber material, characterized by comprising the following steps:

[0035] S1. Preparation of chopped fibers: Cut the scrapped liquid crystal polyarylate rope into segments and disassemble them. Soak them in a neutral detergent at 50-80°C for 20-40 minutes. During the soaking period, rub and scrub the scrapped liquid crystal polyarylate rope to further remove impurities on the scrapped liquid crystal polyarylate rope. Then, remove them, clean them, and dry them. Immerse the scrapped liquid crystal polyarylate rope after preliminary cleaning in 1.5 mol / L dilute sulfuric acid and soak them in an ultrasonic environment at 28KHZ-33KHZ for 15 minutes. The scrapped liquid crystal polyarylate rope is cleaned and its fiber surface roughness is increased, followed by rinsing and drying; the cleaned scrapped liquid crystal polyarylate rope is inspected, and portions with residual impurities are cut off, and the scrapped liquid crystal polyarylate rope is cut to obtain chopped fibers of about 3 mm in length, and the chopped fibers are thoroughly rubbed and broken up; the chopped fibers are placed in a mesh bag, soaked in a modifier solution at a temperature of 50-70°C for 2-5 minutes, removed and naturally drained, and then dried at 80-85°C for 2 hours for later use;

[0036] S2. The natural rubber is first masticated, and then the synthetic rubber and thermoplastic polyurethane elastomer are added and mixed evenly;

[0037] S3. Adding chopped fibers, white carbon black, and nano-clay; in conjunction with the reinforcing agent, the nano-clay can toughen the plastic material to a certain extent;

[0038] S4. Add flame retardants and smoke suppressants;

[0039] When the rubber compound is mixed in an internal mixer, the mixer speed is 40-60RPM and the discharge temperature is about 140°C. When processing conveyor belts, a sulfur vulcanization system can be used in S3 and S4, and 2 parts of sulfur and 1 part of accelerator CZ / DM can be gradually added to the rubber compound. Before vulcanization, a calender is used to combine the rubber compound with a fabric belt core pre-impregnated with an interlayer adhesive (paste) so that the rubber compound covers the fabric belt core from top to bottom. Then, vulcanization is carried out on a flat vulcanizer at 142-145°C, high pressure (such as 15MPa), and 1-3 minutes / mm (total thickness).

[0040] In S1, the modifier solution is a monoalkyl ether phosphate sodium salt or a potassium dodecyl phosphate aqueous solution with a mass concentration of 2-4%.

[0041] In S3, the nanoclay and the chopped fibers obtained in S1 are premixed and sprayed with a silane coupling agent. The addition of the silane coupling agent can prevent or reduce the agglomeration of the chopped fibers during processing, help achieve uniform distribution of the chopped fibers in the rubber system, and improve the tensile strength of the composite material. During production, the chopped fibers can be sprayed with the silane coupling agent and then stirred at high speed, and then mixed with the nanoclay. When mixing into the rubber compound, 1 / 3 of the rubber compound is first mixed with the treated short-term fibers, then white carbon black is added, and the remaining rubber compound is added in two batches for mixing. In this embodiment, the silane coupling agent used is KH-590, and the amount used is 0.5% of the mass of the chopped fibers obtained in S1. Generally speaking, adding more silane coupling agent (such as 1%-2% of the mass of the chopped fibers) can achieve a more complete dispersion effect on the chopped fibers, but excessive use of silane coupling agent in combination with potassium dodecyl phosphate may have an adverse effect on the tensile strength of the material.

[0042] Below, we use the ratio of silane coupling agent and potassium dodecyl phosphate as variables, where the concentration gradient of the modifier (potassium dodecyl phosphate aqueous solution) is 0%, 1%, 2%, 3%, and 4%, and the amount of silane coupling agent (KH-590) (as a percentage of the weight of the chopped fiber) is 0.0%, 0.3%, 0.5%, 0.8%, and 1%. The tensile strength (unit: MPa) of the prepared cover material is tested according to the MT147-95 industry standard. The measurement results are as follows:

[0043]

[0044] It can be seen that the synergistic effect is optimal when the potassium dodecyl phosphate concentration is around 3% and the KH-590 dosage is around 0.8-1% (higher dosages do not provide significant gains), resulting in a higher tensile strength for the cover material. Furthermore, when using a method where the fiber is immersed in the modifying liquid and then naturally drained, a concentration of 4% or higher may result in excessive retention of modifying liquid on the fiber surface, leading to reduced interfacial compatibility and a decrease in the bonding between the chopped fiber and the rubber.

[0045] Comparative Example 1

[0046] Similar to Example 1, the difference is that, under the conditions of a 3% concentration of potassium lauryl phosphate aqueous solution and a KH-590 dosage of 0.8% by weight of the chopped fibers, new liquid crystal polyarylate chopped fibers (monofilament diameter of 60 μm) are used; the tensile strength test average of the covering material is 25.6. During long-term use, the liquid crystal polyarylate rope will experience wear and tear on the fiber surface structure, and during long-term exposure to sunlight and natural erosion by wind and rain, the fiber surface will be eroded (long-term use will cause some cracks and other defects inside the fiber, but when made into chopped fibers, the adverse effects caused by these defects are not obvious and may instead have a positive effect on the bonding between the chopped fibers and the rubber). Compared with the increase in surface roughness of the liquid crystal polyarylate fiber caused by acid washing, the effect of natural erosion on the fiber surface may be more conducive to the reaction between the modifier and the fiber surface, promoting better bonding between the fiber and the rubber.

[0047] Comparative Example 2

[0048] Similar to Example 1, the difference lies in that, under the conditions of a 3% potassium lauryl phosphate aqueous solution and a KH-590 dosage of 0.8% by weight of the chopped fibers, the liquid crystal polyarylate chopped fibers were replaced with nylon chopped fibers of equivalent specifications. The average tensile strength of the cover material was 17.3. This indicates that the high modulus and other properties of the liquid crystal polyarylate chopped fibers significantly improve the tensile strength of the cover material.

[0049] Comparative Example 3

[0050] Similar to Example 1, except that no chopped fibers were added, using a 3% potassium lauryl phosphate aqueous solution and a KH-590 dosage of 0.8% by weight of the chopped fibers. The average tensile strength of the covering material was 15.2. This indicates that the addition of chopped fibers significantly improves the tensile strength of the covering material.

[0051] In general, improving the overall tensile strength of the conveyor belt by increasing the tensile strength of the covering material is highly feasible and has good market prospects.

[0052] The above embodiments are preferred embodiments of the present invention and are used to illustrate the present invention. However, the present invention is not limited to the specific details of the above embodiments. It should be noted that those skilled in the art can make various modifications and improvements without departing from the scope of the present invention, and these modifications and improvements fall within the scope of protection of the present invention.

[0053] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the present invention. Anyone skilled in the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by one of ordinary skill in the art without departing from the spirit and technical principles disclosed herein are intended to be covered by the claims of the present invention.

Claims

1. A liquid crystal polyarylate conveyor belt, characterized in that: The invention comprises a liquid crystal polyarylate fabric belt core and a covering layer fixed to the surface of the belt core by an interlayer adhesive. The liquid crystal polyarylate fabric belt core uses liquid crystal polyarylate fibers as warp yarns and nylon filaments as weft yarns. The covering layer comprises the following components, by weight: 55-70 parts of synthetic rubber, 30-40 parts of natural rubber, 5-15 parts of thermoplastic polyurethane elastomer, 2-6 parts of chopped fibers, 5-8 parts of reinforcing agent, 0.5-0.8 parts of nanoclay, 2-4 parts of smoke suppressant, and 5-10 parts of flame retardant. The chopped fibers contain liquid crystal polyarylate fibers and are modified with sodium monoalkyl ether phosphate or potassium dodecyl phosphate.

2. The liquid crystal polyarylate conveyor belt according to claim 1, characterized in that: The smoke suppressant includes a molybdate smoke suppressant or zinc borate, and the reinforcing agent includes carbon black or white carbon black.

3. The liquid crystal polyarylate conveyor belt according to claim 1, characterized in that: The flame retardant is compounded with aluminum hydroxide and decabromodiphenyl ether, wherein the proportion of decabromodiphenyl ether in the flame retardant is 2-4%.

4. The liquid crystal polyarylate conveyor belt according to claim 1, characterized in that: The length of the chopped fibers is 1-5 mm.

5. The liquid crystal polyarylate conveyor belt according to claim 4, characterized in that: The chopped fibers are made from recycled discarded liquid crystal polyarylate ropes, and the content of liquid crystal polyarylate fibers in the discarded liquid crystal polyarylate ropes is not less than 60%.

6. The liquid crystal polyarylate conveyor belt according to claim 1, characterized in that: The ratio of the synthetic rubber to the natural rubber is 6:4±0.

2.

7. The liquid crystal polyarylate conveyor belt according to claim 6, characterized in that: The synthetic rubber includes styrene-butadiene rubber and / or butadiene rubber.

8. A method for preparing the covering layer material of the liquid crystal polyarylate conveyor belt according to claim 1, characterized in that: The steps include: S1. Preparation of chopped fibers: Cut the scrapped liquid crystal polyarylate rope into segments and disassemble them. Soak them in a neutral detergent at 50-80°C for 20-40 minutes. During the soaking period, rub and scrub the scrapped liquid crystal polyarylate rope to remove impurities on the scrapped liquid crystal polyarylate rope. Then, remove the scrapped liquid crystal polyarylate rope, clean it, and dry it. After preliminary cleaning, immerse the scrapped liquid crystal polyarylate rope in 0.5-2 mol / L dilute sulfuric acid or dilute hydrochloric acid and soak it in an ultrasonic environment for 10-20 minutes to further clean it. The fiber surface roughness of the scrapped liquid crystal polyarylate rope is increased, and then the rope is rinsed and dried. The cleaned scrapped liquid crystal polyarylate rope is inspected, and the portion with residual impurities is cut off. The scrapped liquid crystal polyarylate rope is then cut to obtain chopped fibers with a length of 1-5 mm, and the chopped fibers are thoroughly rubbed and broken up. The chopped fibers are placed in a mesh bag, soaked in a modifier solution at a temperature of 50-70°C for 2-5 minutes, removed and naturally drained, and then dried at 80-85°C for 2 hours for use. S2. The natural rubber is first masticated, and then the synthetic rubber and thermoplastic polyurethane elastomer are added and mixed evenly; S3. Adding chopped fibers, reinforcing agent and nano-clay; S4. Add flame retardants and smoke suppressants.

9. The method for preparing the covering rubber material according to claim 8, characterized in that: In S1, the modifier solution is a monoalkyl ether phosphate sodium salt or a potassium dodecyl phosphate aqueous solution with a mass concentration of 2-4%.

10. The method for preparing the covering rubber material according to claim 8, characterized in that: In S3, the nanoclay and the chopped fibers obtained in S1 are premixed and sprayed with a silane coupling agent, with the amount of the silane coupling agent accounting for 0.5%-1% of the mass of the chopped fibers obtained in S1; the treated chopped fibers are then mixed with 1 / 4-1 / 3 of the rubber compound obtained in S2, followed by adding a reinforcing agent, and then adding the remaining rubber compound in 1-3 batches into the mixing.

Citation Information

Patent Citations

  • Improved fabric for toothed power transmission belt and belt

    CN102472363A

  • Inflaming retarding non-toxic cable material with high temperature resistance

    CN108410045A

  • Rubber composition, laminate body, and conveyer belt

    CN108779294A

  • High-strength flame-retardant elastic fabric and preparation method thereof

    CN109159521A

  • Antistatic TPU belt

    CN110628208A